Macroeconomic risks across the globe due to the Spanish flu - Roberto A. De Santis; Wouter Van der Veken (European Central Bank (ECB), 2020)
We characterise the distribution of expected GDP growth during the Great Influenza Pandemic (known also as Spanish Flu) using a non-linear method in a country panel setting. We show that there are non-negligible risks of large GDP losses with the 5% left tail of the distribution suggesting a drop in the typical country's real per capita GDP equal to 29.1% in 1918, 10.9% in 1919 and 3.6% in 1920. Moreover, the fall in per capita GDP after the Spanish flu was on average particularly large in low-income countries. Particularly, the size of the GDP drop in the lower tail of the distributions is high for higher income countries and immense for lower income countries. As for the United States, the estimated size of the recession in the lower tail of the distribution following the Spanish flu is not negligible.
Keywords: E3; I0; 330; Spanish flu; Pandemic disease; Macroeconomic risks; Non-linear models